Challenge of a dual burden in rapidly aging Delaware: Comorbid chronic conditions and subjective cognitive decline - Sangeeta Gupta (PLOS Global Public Health, 2022)
Background Epidemiologic trends forecast a “dual burden”- increase in both physical chronic diseases and Alzheimer’s disease (AD)- for Delaware. Estimating the burden and characteristics of this “dual burden” is critical. Cognizant of the unavailability of precise models to measure AD, SCD—a population-based measure- was used as an alternative. The primary objective was to delineate selected chronic conditions among Delaware adults with SCD in order to present: (i) prevalence of SCD by select sociodemographic characteristics, (ii) compare the prevalence of chronic conditions among people with and without SCD, and (iii) compare the prevalence of SCD associated functional limitations in Delawareans with and without comorbid chronic conditions. Methods Combined data (2016 and 2020) for Delaware were obtained from the Behavioral Risk Factor Surveillance System. Analyses included 4,897 respondents aged 45 years or older who answered the SCD screening question as “yes” (n = 430) or “no” (n = 4,467). Descriptive statistics examined sociodemographic characteristics and chronic conditions in Delawareans with and without SCD. Results Overall, 8.4% (CI: 7.4–9.5) of Delaware adults reported SCD. Delawareans with SCD were more likely to be in the younger age group (45–54 years), less educated, low income and living alone. Over 68 percent had not discussed cognitive decline with a health care professional. More than three in four Delawareans with SCD had a 1.5 times higher prevalence of having any one of the nine select chronic conditions as compared to those without SCD. Adults with SCD and at least one comorbid chronic condition were more likely to report SCD-related functional limitations. Conclusions Delaware cannot afford to postpone public policies to address the dual burden of SCD and chronic conditions. Results from this study can help public health stakeholders in Delaware to be informed and prepared for the challenges associated with cognitive decline and comorbidity.